Szkoła życia. Wektory aksjologiczne w „Pamiętniku” Janusza Korczaka - Rudnicki , Zbigniew (Studia Edukacyjne, 2023)
Humanity found itself once again in a deep crisis. Its political and ecological dimensions are most frequently recognized, and recently its ecological ones. This provokes fundamental questions and a search for adequate answers, especially in the subtle realm of spiritual matters, where we also find values. It seems necessary to reconsider the effort to reflect on rudimentary issues and to turn to classical texts. The profound thoughts of Janusz Korczak in the Ghetto Diary, his last, very personal, and multi-threaded work as the “Old Doctor”, appear to be an excellent source here.